Introduction to Human Resource Management A Guide to HR in Practice. - Leatherbarrow, Charles; Fletcher, Janet; Currie, Donald; Chartered Institute of Personnel and Development (London : Chartered Institute of Personnel and Development, 2010)
Offering a practical approach to human resource and personnel issues, this book takes account of the fact that, in addition to developing a sound understanding of the relevant underlying ideas, students also need to develop competence in their practical application.
Previous ed.: published as by Donald Currie. 2006.
Includes bibliographical references and index.
Keywords: Personnel management; Business and Management